THE ADMIRAL OR THE ARISTOCRAT? In the search for an 'inventor' of electronic computers, who should be crowned Queen of Computing? - Fara, Patricia (History Today, 2023)
The article discusses the debate over who should be credited with the invention of the first electronic computer, with the U.S and Great Britain being the main contenders. It mentions that while the British version focuses on the Colossus machine and the work of Alan Turing, the American version centers on the ENIAC (Electronic Numerical Integrator and Calculator) machine.